Protection and Punishment of Domestic Violence Victims by the Gorontalo City Resort Police Department - Sifat, Ditasya Amalia R.; W. Badu, Lisnawaty; Mandjo, Julius T. (Universitas Negeri Gorontalo, 2024)
The purpose of this study is to analyze the legal protection provided by Gorontalo City Resort Police to victims of domestic violence (KDRT) and evaluate the extent to which the protection is in accordance with applicable legal provisions. Based on the study of the implementation of legal protection, there is a discrepancy between the policy stipulated in Law No. 23/2004 on the Elimination of Domestic Violence and the practice in the field. This research uses a qualitative approach with the method of interviewing the local police and analyzing the data obtained. The results showed that the protection provided by the police was limited to the trial process, without any further assistance for victims, especially in post-incident trauma recovery. The main factor inhibiting further assistance is the limited budget owned by the police. Therefore, this study suggests the need for synergy between the police, social services, protection agencies, and other related parties to provide more comprehensive protection to victims of domestic violence, as well as strengthen the implementation of police duties in protecting the community